Validity And Practicality of Biodiversity Textbooks Based on Science, Technology, Environment, Society (STES) to Train Students’ Critical Thinking Skills - Fauziah, Anisa; Rachmadiarti, Fida (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
A textbook development research on biodiversity topic was aimed to make a valid STES-based (Science, Technology, Environment, Society) biodiversity textbook for training students’ critical thinking skills which were assessed through the contents, presentations, and linguistics. The method used for this research was ADDIE development models, validity, and readability. Validity was tested by an educational expert, a biodiversity expert, and a 10th-grade biology teacher. The readability obtained by determining its’ readability level based on a Fry Graph, which was counting the number of sentences and syllables of 100-words sample. The result showing that a STES-based biodiversity textbook is appropriate for training 10th-grade students’ critical thinking skills. Validity was interpreted as highly valid at a score of 3.73. The textbook’s readability score was at the 10th level, which means that a biodiversity textbook is proper to be read by 10th –grade students. Keywords: textbook, biodiversity, STES, critical thinking.